Therapeutic efficacy of quercetin enzyme-responsive nanovesicles for the treatment of experimental colitis in rats. (February 2015) - Castangia, Ines; Nácher, Amparo; Caddeo, Carla; Merino, Virginia; Díez-Sales, Octavio; Catalán-Latorre, Ana; Fernàndez-Busquets, Xavier; Fadda, Anna Maria; Manconi, Maria
Graphical abstract: Abstract: Biocompatible quercetin nanovesicles were developed by coating polyethylene glycol-containing vesicles with chitosan and nutriose, aimed at targeting the colon. Uncoated and coated vesicles were prepared using hydrogenated soy phosphatidylcholine and quercetin, a potent natural anti-inflammatory and antioxidant drug. Physicochemical characterization was carried out by light scattering, cryogenic microscopy and X-ray scattering, the results showing that vesicles were predominantly multilamellar and around 130 nm in size. The in vitro release of quercetin was investigated under different pH conditions simulating the environment of the gastrointestinal tract, and confirmed that the chitosan/nutriose coating improved the gastric resistance of vesicles, making them a potential carrier system for colon delivery. The preferential localization of fluorescent vesicles in the intestine was demonstrated using the In Vivo FX PRO Imaging System. Above all, a marked amelioration of symptoms of 2, 4, 6-trinitrobenzenesulfonic acid-induced colitis was observed in animals treated with quercetin-loaded coated vesicles, favoring the restoration of physiological conditions. Therefore, quercetin-loaded chitosan/nutriose-coated vesicles can represent a valuable therapeutic tool for the treatment of chronic intestinal inflammatory diseases, and presumably a preventive system, due to the synergic action of antioxidant quercetin and beneficial prebiotic effects of the chitosan/nutriose complex.